3rd International Conference on Thermal Issues in Machine Tools (ICTIMT2023) - Ihlenfeldt, Steffen (Lecture Notes in Production Engineering, 2023)
This open access conference proceedings contains all the papers presented at the ICTIMT 2023, the 3rd International Conference on Thermal Issues in Machine Tools. The event takes place in Dresden, the capital of Saxony, from March 21-23 2023. The conference is organized by the Chair of Machine Tools Development and Adaptive Controls of the Technische Universität Dresden.